Concise encyclopedia of American Indian - Grant, Bruce; Bjorklund, Lorence F. (Bonanza Books New York, 1989)
Presents descriptive alphabetical entries on Indian tribes, territories, customs, tools, activities, and famous leaders.
Keywords: Indians of North America